Penggunaan Media Roda Berputar materi Nilai-Nilai Pancasila Pada Hasil Belajar Siswa Kelas IV SD Tanwirul Afkar - Azuma Zuhro, Fadilah; Eka Tiyas Rifayanti, Zuni (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The use of spinning wheel media in the context of education has become a focal point in efforts to improve student learning outcomes. This study aims to explore the use of spinning wheel media on the Pancasila values material and its impact on the learning outcomes of fourth-grade students at SD Tanwirul Afkar Surabaya using a qualitative approach. This research uses a case study with fourth-grade participants. Data were collected through observation, interviews, documentation, and learning outcomes. The researchers showed that the use of spinning wheel media effectively in the learning concept, enhancing student engagement, and better understanding. The positive response from students to this media increases during the learning process. A significant improvement in students' understanding and achievement confirms the effectiveness of the spinning wheel media as an educational aid. This conclusion emphasizes the importance of the rotating wheel media in learning strategies to enhance student learning outcomes.